Kesejahteraan Mental Sebagai Investasi Strategis dalam Manajemen Sumber Daya Manusia - Irvan Setiawan; Deden Sutisna; Yenny Maya Dora; Nurul Hermina (SENTRI: Jurnal Riset Ilmiah, 2026)
The issue of employee well-being is increasingly becoming a major concern in human resource management as work demands and modern organizational dynamics increase. High work pressure, changes in work systems, and post-pandemic uncertainty have the potential to worsen the psychological condition of employees if not balanced with adequate work resources. This study aims to analyze the role of supervisor support, work-life balance, and meaningful work on employee well-being as a strategic investment in human resource management. This study uses a descriptive-exploratory qualitative approach with purposive sampling techniques. Data were collected through in-depth interviews and non-participant observation of employees and line managers, supported by secondary data in the form of relevant scientific literature and institutional publications. The results show that supervisor support plays an important role in creating psychological safety, work-life balance contributes to emotional stability, and meaningful work strengthens employee engagement and mental resilience. Simultaneously, these three variables function as complementary job resources in improving employee well-being, as explained in the Job Demands–Resources (JD-R) Theory framework. Meaningful Work acts as a “psychological anchor.” When organizational dynamics create uncertainty (such as changes in work systems), meaningful work ensures that employees remain connected to their professional identity, thereby preventing mental disorientation. This study concludes that strengthening psychosocial resources in the workplace is an effective strategy for improving employee well-being and supporting the sustainability of organizational performance and productivity.